Exploring Processes of Reading and Meaning-making in Second Grade Classrooms: Part 1 - Bahuguna, Pooja (Voices of Teachers and Teacher Educators, 2023)
This paper presents details of Part 1 of a significant classroom-based research study This descriptive study explored reading and meaning-making processes in second grade classrooms. The objective of the study was to explore and describe the nature and focus of reading instructions, nature and quality of literacy environment and effectiveness of the reading instructions in order to help students become engaged readers whose reading attempts are meaning-driven, lused observation on field notes, journal entries and interviews with teachers as the sources of data collection. The findings are interesting, they lead us to think and reflect about reading comprehension instructions in early primary grades in Indian context